The E.T.PACK project: Towards a fully passive and consumable-less deorbit kit based on low-work-function tether technology. (December 2020) - Sánchez-Arriaga, G.; Naghdi, S.; Wätzig, K.; Schilm, J.; Lorenzini, E.C.; Tajmar, M.; Urgoiti, E.; Castellani, L. Tarabini; Plaza, J.F.; Post, A.
Abstract: The Electrodynamic Tether Technology for Passive Consumable-less Deorbit Kit (E.T.PACK) is a project aimed at the development of a deorbit kit based on low-work-function Tether (LWT) technology, i.e., a fully passive and electrically floating system made of a long conductive tape coated with a low-work-function material. The LWT interacts passively with the environment (ambient plasma, magnetic field, and solar radiation) to exchange momentum with the planet's magnetosphere, thus enabling the spacecraft to de-orbit and/or re-boost without the need for consumables. The main goal is to develop a deorbit kit and related software with Technology Readiness Level 4 and promote a follow-up project to carry out an in-orbit experiment. The planned kit in the experiment has three modes of operation: fully passive LWT and conventional electrodynamic tether equipped with an active electron emitter in passive and active modes. Several activities of the project pivot around the C 12 A 7 : e − electride, which will be used in four hardware elements: (i) LWT (ii) hollow cathode, (iii) photo-enhanced thermionic emission device to convert solar photon energy into electrical energy, and (iv) a hollow cathode thruster. These elements, some of which do not belong to the deorbit kit, are synergetic with the main stream of the project and common to some tether applications like in-orbit propulsion and energy generation. This work explains the activities of E.T.PACK and the approach for solving its technological challenges. After reviewing past progresses on electrodynamic tethers and thermionic materials, we present a preliminary concept of the kit for the in-orbit experiment, some simulation results, and the key hardware elements. Highlights: The work plan of the E.T.PACK project is presented. Goal: development of a deorbit kit based on a Low Work Function Tether (LWT). The kit has 3 modes: as LWT and as standard bare tether in active and passive modes. The performance of the kit is studied through numerical simulations. The C12A7:e- electride is applied to four hardware elements.